(untitled) (Revista Brasileira Multidisciplinar, 2026)
Phytocosmetics offer a sustainable alternative to conventional skin care cosmetics, particularly due to their natural origin and the presence of bioactive compounds that provide therapeutic benefits. The aim of this study was to present a systematic literature review on the possibilities of prevention and treatment of facial skin using phytocosmetics. A search of articles published between 2019 and 2023 was conducted in the Science Direct and Wiley Online Library databases using the keywords "phytocosmetics" and "facial skin". The results highlight the effectiveness and safety of various phytocosmetic formulations, revealing their benefits in combating skin aging, hyperpigmentation, and oiliness. Additionally, the reviewed studies underscore the positive acceptability of these products among the target audience of clinical trials. Consequently, this review reinforces the relevance of phytocosmetics as a safe, effective, and sustainable option for facial skin care. However, it emphasizes the need for further research and clinical studies to deepen the understanding of these products and explore their potential in different dermatological contexts and conditions.